Z načrtnim strokovnim delom z gozdovi najbolje ohranjamo naravo - Veselič, Živan (Gozdarski vestnik, 2011)
Forest is by far the most important at least mostly preserved element of the Slovenian landscape. The close-to-nature forestry keeps the forest as natural as possible, acquiring the goods from it at the same time. The close-to-natureforestry is therefore a basis for nature conservation in the whole landscape. The close-to-nature forestry as a complex manner of working with forest in Slovenia was implemented by Prof. Dr. Dušan Mlinšek, one of thepioneers of the close-to-nature forestry in the world. The close-to-nature forest management is performed in Slovenia for over 50 years. Founding the Natura 2000 network has played an important role for nature conservation in the whole EU as well as in Slovenia. The measures for achieving protection goals in Natura 2000 areas being planned in individual sectors' plans represent a Slovenian specialty. The measures in forests are thus planned in forest management plans and long-term wild game management plans. We collected opinions on the previous work for planning of measures for attaining protection goals in the Natura 2000 forests and propositions for even better work in this field in the future.
Keywords: sonaravno gozdarstvo; gozdnogospodarsko načrtovanje; varstvo narave; environmental protection; Natura 2000; Slovenia; Slovenija